Maintenance electroconvulsive therapy in schizophrenia - Krepela, Josef; Hosak, Ladislav; Pachlova, Barbora; Hrdlicka, Michal (Psychiatria Danubina, 2019)
BACKGROUND: The aim of our retrospective naturalistic observational study was to describe the use of maintenance electroconvulsive therapy (M-ECT) in chronic pharmacoresistant schizophrenia. SUBJECTS AND METHODS: We delineated 19 cases of chronic pharmacoresistant schizophrenia (females N=12) recently treated with maintenance electroconvulsive therapy at the Havlickuv Brod Psychiatric Hospital in the Czech Republic. Demographic, clinical and treatment variables were recorded. RESULTS: M-ECT, when applied weekly to monthly mostly over a period of several years, was of no benefit in the treatment of chronic hallucinations and/or delusions. However, it did prove beneficial (p<0.001) in removing chronic serious symptoms like suicidal or violent behavior, automutilation, refusal of food or liquids, stupor or catatonia. Even though almost all of our patients remained hospitalized, we were nonetheless able to transfer them to an unlocked psychiatric ward and let them out for walks or occupational therapy with almost no need for using restraint. No serious adverse side effects of M-ECT were found. CONCLUSIONS: Our study is limited by using only one simple standardized measurement (Clinical Global Impression - Severity) that was retrospective. Another limitation of our retrospective study was that the subjects had not been regularly tested for their cognitive functions. According to our results, M-ECT mitigates the impact of the disease and improves social functioning of the patients. M-ECT does not treat chronic schizophrenia but does make the lives of patients more tolerable. We suggest further research into M-ECT and its clinical application in chronic pharmacoresistant schizophrenia.
Keywords: katatonie; schizofrenie; elektrokonvulzívní terapie; Electroconvulsive Therapy; Female; retrospektivní studie; Humans; ženské pohlaví; Česká republika; mužské pohlaví; výsledek terapie; lidé; Male; Retrospective Studies; Schizophrenia; Treatment Outcome; Catatonia; Czech Republic